PROSES SCAFFOLDING BERDASARKAN DIAGNOSIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Marlin Blandy Mananggel (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2022)
The purpose of this study was to describe the process and the form of scaffolding to overcome students' difficulties in solving mathematics world problem. This study used a descriptive-explorative qualitative research design. In this case, the researcher is the primary instrument. Data collection uses diagnostic tests, comprehension tests, interview guidelines and scaffolding guidelines, and also field notes. Triangulation of data sources is applied to check the validity of the data. Based on the results of the diagnosis, the researcher carried out level 2 and level 3 scaffolding with four components, namely explaining, reviewing, restructuring, and developing conceptual thinking. The results of the comprehension test showed that by presenting scaffolding, students' difficulties had been reduced, and there were even two subjects who had no more difficulties, they are subjects from the high group. Meanwhile the two other subjects had mistaken in determined the roots of the quadratic equation and the other subjects had mistaken in written the conclusions.